TOXICITY TEST OF Annona muricata L. LEAF EXTRACT AS A BIOPESTICIDE AGAINST MORTALITY OF Spodoptera frugiperda J. E. Smith - Khoirunnisya, Hylda Aulia; Afifah, Lutfi; Surjana, Tatang; Yustiano, Anton (JURNAL AGROPLASMA, 2022)
Spodoptera frugiperda is a new invasive pest that can cause losses in corn production, so control measures are needed to suppress its population. The purpose of this study was to obtain the best concentration of botanical pesticide from soursop leaves extract against the fall armyworm (S. frugiperda). The method used is experimental method using a single factor Completed Randomized Design (RAL) consisting of 7 treatments with 4 replications: A (Control); B (Insecticide deltamethrin 1 ml/lt); C (A. muricata leaves extract 20 gr/lt); D (A. muricata leaves extract 30 gr/lt); E (A. muricata leaves extract 40 gr/lt); F (A. muricata leaves extract 50 gr/lt); G (A. muricata leaves extract 60 gr/lt). The treatment effect was analyzed with Analysis of Variance (ANOVA). If the 5% level F test showed significant results, then it proceeded with the DMRT (Duncan Multiple Range Test) further test at a 5% significance level to determine the best treatment. The results achieved from this study were the concentration of soursop leaves extract 60 gr/lt was able to cause 50% mortality of S. frugiperda in less than one day based on the analysis of probit LT50, inhibiting the larvae from stopping eating with a percentage of 75% at 1 Day After Application (DAA), gave the highest mortality of 85% in 3 DAA. A. muricata leaves extract with a concentration of 60 g/lt was recommended to be used because it gave the best results that were not significantly different from the use of synthetic insecticides against S. frugiperda.